OPTIMIZATION OF MULTI FACTORS FOR INJECTION-MOULDED MICRO GEAR VIA NUMERICAL SIMULATION INTEGRATED WITH THE TAGUCHI METHOD AND PRINCIPAL COMPONENT ANALYSIS - Mehat, N.M. (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
Many factors need to be considered in producing micro gear by means of injection moulding process including material selection, part and mould design as well as processing parameters. Inappropriate combination of these factors can cause numerous production problems such as occurring of defects, long lead time, much scrap and high production cost. Therefore, the aim of this study is to evaluate the effects of different material for micro gear, gate types, size of gear as well as processing parameters on the multi quality characteristics of the micro gear. The simulation was conducted by integration of Taguchi L27 orthogonal array and principal component analysis. The result of main effect analysis exhibited that the optimal combination of factors that resulted in minimum sink index, volumetric shrinkage and deflection was A3B3C2D3E1F1G1H1I3. Meanwhile, from the ANOVA, gate type was found out to be the most significant factor in minimizing the multi quality characteristic of the simulated micro gear. The findings of this study should be benefited to the gear industry particularly in improving the quality of micro gear where the use of micro gear in microsystem is accelerating nowadays. Â© 2020. All rights reserved.